Longitudinal genomic profiling using liquid biopsies in metastatic nonsquamous NSCLC following first line immunotherapy - Haolun Ding; Min Yuan; Yaning Yang; Xu Steven Xu (npj Precision Oncology)
Abstract Tumor genomic profiling is often limited to one or two timepoints due to the invasiveness of tissue biopsies, but longitudinal profiling may provide deeper clinical insights. Using ctDNA data from IMpower150 study, we examined genetic changes in metastatic non-squamous NSCLC post-first-line immunotherapy. Mutations were most frequently detected in TP53, KRAS, SPTA1, FAT3, and LRP1B at baseline and during treatment. Mutation levels rose prior to radiographic progression in most progressing patients, with specific mutations (SPTA1, STK11, KEAP1, SMARCA4, TBX3, CDH2, and MLL3) significantly enriched in those with progression or nondurable response. However, ctDNA’s role in detecting hyperprogression and pseudoprogression remains uncertain. STK11, SMARCA4, KRAS, SLT2, and KEAP1 mutations showed the strongest correlation with poorer overall survival, while SMARCA4, STK11, SPTA1, TBX3, and KEAP1 mutations correlated with shorter progression-free survival. Overall, longitudinal liquid biopsy profiling provided valuable insights into lung cancer biology post-immunotherapy, potentially guiding personalized therapies and future drug development.